Purple nutsedge (Cyperus rotundus) response to postemergence herbicides varies with mode of action and plant growth stage - Vijay Varanasi; Taghi Bararpour; Partson Mubvumba; Reginald Fletcher; Krishna Reddy (Weed Technology)
Purple nutsedge is a competitive and persistent perennial weed in the agronomic and horticultural cropping systems of the southeastern United States. Its management is a challenge during the growing season due to its ability to propagate vegetatively through underground rhizomes and tubers. Therefore, effective herbicide programs are needed that can check the spread of purple nutsedge and protect crop yields. Greenhouse experiments were conducted in 2024 to evaluate the response of purple nutsedge at two different growth stages (10 to 15 cm and 15 to 20 cm heights) to herbicides currently labeled for use in Mississippi cropping systems. Herbicides tested were glyphosate at 1,260 g ai ha–1, glufosinate at 672 g ai ha–1, bentazon at 1,680 g ai ha–1, halosulfuron at 69.5 g ai ha–1, and trifloxysulfuron at 6.9 g ai ha–1. Glyphosate was the most effective herbicide against purple nutsedge, providing >90% control, followed by halosulfuron, which provided 70% to 90% control at both growth stages. New shoot emergence was highest when glufosinate and bentazon were applied, and no new shoots emerged when glyphosate and halosulfuron were applied. More new shoots were observed when glufosinate and bentazon were applied when plants were 15 to 20 cm high compared to 10 to 15 cm. Shoot regrowth at 21 d after cutting the aboveground shoots indicated similar trends. A reduction of >90% in shoot and root biomass was observed when glyphosate, halosulfuron, and trifloxysulfuron were applied, whereas glufosinate and bentazon applications resulted in 50% less biomass reduction. Overall, herbicide efficacy against purple nutsedge was greater when plants were treated at the recommended height of 10 to 15 cm rather than 15 to 20 cm. The study results indicated that both herbicide mode of action and application timing are important for better purple nutsedge management in cropping systems.